Menthol Cigarettes, Tobacco Dependence, and Smoking Persistence: The Need to Examine Enhanced Cognitive Functioning as a Neuropsychological Mechanism. Issue 4 (14th December 2018) - Jao, Nancy C; Tan, Marcia M; Matthews, Phoenix A; Simon, Melissa A; Schnoll, Robert; Hitsman, Brian
Abstract: Introduction: Despite the overall decline in the prevalence of cigarette use in the United States, menthol cigarette use among smokers is rising, and evidence shows that it may lead to more detrimental effects on public health than regular cigarette use. One of the mechanisms by which nicotine sustains tobacco use and dependence is due to its cognitive enhancing properties, and basic science literature suggests that menthol may also enhance nicotine's acute effect on cognition. Aims and Methods: The purpose of this review is to suggest that the cognitive enhancing effects of menthol may be a potentially important neuropsychological mechanism that has yet to be examined. In this narrative review, we provide an overview of basic science studies examining neurobiological and cognitive effects of menthol and menthol cigarette smoking. We also review studies examining menthol essential oils among humans that indicate menthol alone has acute cognitive enhancing properties. Finally, we present factors influencing the rising prevalence of menthol cigarette use among smokers and the importance of this gap in the literature to improve public health and smoking cessation treatment. Conclusions: Despite the compelling evidence for menthol's acute cognitive enhancing and reinforcing effects, this mechanism for sustaining tobacco dependence and cigarette use has yet to be examined and validated among humans. On the basis of the basic science evidence for menthol's neurobiological effects on nicotinic receptors and neurotransmitters, perhaps clarifying menthol's effect on cognitive performance can help to elucidate the complicated literature examining menthol and tobacco dependence. Implications: Menthol cigarette use has continued to be a topic of debate among researchers and policy makers, because of its implications for understanding menthol's contribution to nicotine dependence and smoking persistence, as well as its continued use as a prevalent flavoring in tobacco and nicotine products in the United States and internationally. As international tobacco regulation policies have begun to target menthol cigarettes, research studies need to examine how flavoring additives, specifically menthol, may acutely influence neurobiological and cognitive functioning as a potential mechanism of sustained smoking behavior to develop more effective treatments.